Differential impact of syncope on the prognosis of patients with acute pulmonary embolism: a systematic review and meta-analysis. (17th October 2018) - Barco, Stefano; Ende-Verhaar, Yvonne M; Becattini, Cecilia; Jimenez, David; Lankeit, Mareike; Huisman, Menno V; Konstantinides, Stavros V; Klok, Frederikus A
Abstract: Aims: Controversial reports exist in the literature regarding the prognostic role and therapeutic implications of syncope in patients with acute pulmonary embolism (PE). We conducted a systematic review and meta-analysis to investigate the association between syncope and short-term adverse outcomes, taking into account the presence or absence of haemodynamic compromise at acute PE presentation. Methods and results: The literature search identified 1664 studies, 29 of which were included for a total of 21 956 patients with PE ( n  = 3706 with syncope). Syncope was associated with higher prevalence of haemodynamic instability [odds ratio (OR) 3.50; 95% confidence interval (CI) 2.67–4.58], as well as with echocardiographic signs of right ventricular (RV) dysfunction (OR 2.10; CI 1.60–2.77) at presentation. Patients with syncope had a higher risks of all-cause early (either in-hospital or within 30 days) death (OR 1.73; CI 1.22–2.47) and PE-related 30-day adverse outcomes (OR 2.00; CI 1.11–3.60). The absolute risk difference (95% CI) for all-cause death was +6% (+1% to +10%) in studies including unselected patients, but it was −1% (−2% to +1%) in studies restricted to normotensive patients. We observed no prognostic impact of syncope in studies with a lower score at formal quality assessment and in those conducted retrospectively. Conclusion: Syncope as a manifestation of acute PE was associated with a higher prevalence of haemodynamic instability and RV dysfunction at presentation, and an elevated risk for early PE-related adverse outcomes. The association with an increased risk of early death appeared more prominent in studies including unselected patients, when compared with those focusing on normotensive patients only.